(untitled) (Satyawati Nagar, New Delhi, 2002)
Contents of material: Introduction. Library networking. Community information networks. Information management tools for network environment. Inter-library loan and document delivery. Implications of library networking. LAN-based sofware in library systems. Future of networks.
Keywords: Computer networks.,Library information networks